Urinary I-FABP, L-FABP, TFF-3, and SAA Can Diagnose and Predict the Disease Course in Necrotizing Enterocolitis at the Early Stage of Disease - Stepan Coufal; Alena Kokesova; Helena Tlaskalova-Hogenova; Barbora Frybova; Jiri Snajdauf; Michal Rygl; Miloslav Kverka (Journal of Immunology Research)
Necrotizing enterocolitis (NEC) is a severe gastrointestinal disease affecting mainly preterm newborns. It is characterized by unexpected onset and rapid progression with specific diagnostic signs as pneumatosis intestinalis or gas in the portal vein appearing later in the course of the disease. Therefore, we analyzed diagnostic and prognostic potential of the markers of early NEC pathogenesis, such as excessive inflammatory response (serum amyloid A (SAA)) and gut epithelium damage (intestinal and liver fatty acid-binding protein (I-FABP and L-FABP, respectively) and trefoil factor-3 (TFF-3)). We used ELISA to analyze these biomarkers in the urine of patients with suspected NEC, either spontaneous or surgery-related, or in infants without gut surgery (controls). Next, we compared their levels with the type of the disease (NEC or sepsis) and its severity. Already at the time of NEC suspicion, infants who developed NEC had significantly higher levels of all tested biomarkers than controls and higher levels of I-FABP and L-FABP than those who will later develop sepsis. Infants who will develop surgery-related NEC had higher levels of I-FABP and L-FABP than those who will develop sepsis already during the first 6 hours after the abdominal surgery. I-FABP was able to discriminate between infants who will develop NEC or sepsis and the SAA was able to discriminate between medical and surgical NEC. Moreover, the combination of TFF-3 with I-FABP and SAA could predict pneumatosis intestinalis, and the combination of I-FABP, L-FABP, and SAA could predict gas in the portal vein or long-term hospitalization and low SAA predicts early full enteral feeding. Thus, these biomarkers may be useful not only in the early, noninvasive diagnostics but also in the subsequent NEC management.